Study of clinical etiological and radiological profile of UTI cases - Vaidya, Sunil S.; Gaikwad, Shahaji Y. (International Journal of Contemporary Pediatrics, 2018)
Background: Fever and significant bacteriuria and pyuria in children with undocumented sources of infections must be presumed to be symptoms of pyelonephritis, an invasive infection of the renal parenchyma requiring prompt treatment. The present study is undertaken to study of clinical, etiological and radiological profile of children with culture positive UTI. Methods: This study is being performed on children with culture positive Urinary tract infection admitted or attending OPD at department of Paediatrics during the study duration were included in the present study. Results: The highest incidence of UTI in present study was found to be 52.25% in the age group of children below 2 years. E-coli (75%) was the commonest organism found in urine culture in all age groups. Sensitivity, negative predictive value and positive predictive value of renal ultrasonography in detecting VUR was very poor, supporting the impression that renal USG is deficient in accurately excluding VUR. VUR are common in Culture positive UTI, milder grade are more common which are more likely to be missed by renal USG, thus stressing the need of MCU in children of culture positive UTI. Conclusions: Urine examination and culture and sensitivity must be a part and partial in evaluating child with fever without focus. As the scope of USG in detecting VUR is low, MCU must be done in all cases of UTI -5years irrespective of USG finding.